IN UZBEKISTAN INDIRECTLY TAXES CORRECTION DOING : SOCIAL PROTECTION AND BUDGET SUSTAINABILITY BALANCE (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
The study provides an in-depth analysis of the relationship between the principles of macroeconomic stability and social justice in the reform of the indirect tax system in the Republic of Uzbekistan. The study examines the impact of reducing the value-added tax (VAT) rate, expanding excise tax objects, and digitizing tax administration on the composition of budget revenues based on data for the last three years (2022–2024) and strategic forecasts until 2026. The regressive nature of indirect taxes and their impact on the consumer basket of low-income groups of the population are assessed from the point of view of the effectiveness of the social protection system. The report presents scientifically based recommendations for maintaining the budget deficit at 3 percent of GDP and increasing the targeting of social spending, as well as modern econometric models for forecasting tax revenues.